Progress and Trends of Spatial Clustering Research in Producer Services. Issue 6 (May 2019) - Qi, Luhui; Long, Yu; Luo, Yubin
Abstract: With the low-end industries continuous migration to low-income countries, China has the high requirement to upgrade the level of productive services. This research discussed the spatial aggregation of global producer services from three major aspects, research history, levels and conclusions. and explored the following characteristics: the research perspective shifts from the spatial characteristics of geography-based summaries to the multi-factors of industrial economy, society, and enterprise management. The research level is based on macro research, and gradually moves toward medium and onlookers to better guide urban construction; research conclusions are distributed from static spatial distribution to the dynamic analysis causes of industrial decision-making. In the future, under the support of informatization and big data, the research on the spatial aggregation of productive service industry will inevitably shift from the analysis of historical spatial characteristics to the analysis of corporate spatial decision-making in the context of analyzing social and economic development trends. The development path can better guide the dynamic development of the space gathering of the industry in the future by considering Chinese characteristics.